The Placement of Children Following Non‐Accidental Head Injuries: Are They Protected From Further Harm?1. (13th September 2014) - Stephens, Amanda; Oates, Kim; Appleton, Jane V.; Sidebotham, Peter
Key Practitioner Messages: Most children with non‐accidental head injury are removed from their parents in New South Wales, Australia. Despite high rates of removal, re‐notification to the statutory authority, including for risk of physical harm, remains high. Further research is needed on how placement might affect ongoing involvement of non‐accidental head injury victims with the statutory authority.